Answer: 16)
(17)
(18)
(19) 3x - 18
Explanation:
Inverse is when you swap the x's and y's and then solve for y
16) Given: y = x²
Swapped: x = y²
![\bold{√(x) =y}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v0jxlfcjq96xlk62funkwmnao3t05rg9vk.png)
17) Given: y = 2x + 4
Swapped: x = 2y + 4
x - 4 = 2y
![\bold{(x-4)/(2)=y}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yt6z070y1y83n5pvlmwh6dgjqn4otwjwk4.png)
18) Given: y = (x + 2)²
Swapped: x = (y + 2)²
√x = y + 2
![\bold{√(x)-2=y}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/h4w838n91fzocgcx9xdmr1rk0nusl4ouq2.png)
19) Given:
![y=(1)/(3)x+6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ijen6og6fdiv63wgxc4anan7tq7eyqa4ke.png)
Swapped:
![x=(1)/(3)y+6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gohbm9trtokc7ngatwz7z9ngw6e6smfgeh.png)
![x - 6 = (1)/(3)y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dcd7ladmjnh4qje79pocrmu4c2ywprc1f4.png)
3(x - 6) = y
3x - 18 = y